Increased Expression of Viral Sensor MDA5 in Pancreatic Islets and in Hormone-Negative Endocrine Cells in Recent Onset Type 1 Diabetic Donors - Nigi, Laura; Brusco, Noemi; Grieco, Giuseppina E.; Fignani, Daniela; Licata, Giada; Formichi, Caterina; Aiello, Elena; Marselli, Lorella; Marchetti, Piero; Krogvold, Lars; Jorgensen, Knut Dahl; Sebastiani, Guido; et al. (Frontiers in Immunology, 2022)
The interaction between genetic and environmental factors determines the development of type 1 diabetes (T1D). Some viruses are capable of infecting and damaging pancreatic β-cells, whose antiviral response could be modulated by specific viral RNA receptors and sensors such as melanoma differentiation associated gene 5 (MDA5), encoded by the IFIH1 gene. MDA5 has been shown to be involved in pro-inflammatory and immunoregulatory outcomes, thus determining the response of pancreatic islets to viral infections. Although the function of MDA5 has been previously well explored, a detailed immunohistochemical characterization of MDA5 in pancreatic tissues of nondiabetic and T1D donors is still missing. In the present study, we used multiplex immunofluorescence imaging analysis to characterize MDA5 expression and distribution in pancreatic tissues obtained from 22 organ donors (10 nondiabetic autoantibody-negative, 2 nondiabetic autoantibody-positive, 8 recent-onset, and 2 long-standing T1D). In nondiabetic control donors, MDA5 was expressed both in α- and β-cells. The colocalization rate imaging analysis showed that MDA5 was preferentially expressed in α-cells. In T1D donors, we observed an increased colocalization rate of MDA5-glucagon with respect to MDA5-insulin in comparison to nondiabetic controls; such increase was more pronounced in recent-onset with respect to long-standing T1D donors. Of note, an increased colocalization rate of MDA5-glucagon was found in insulin-deficient-islets (IDIs) with respect to insulin-containing-islets (ICIs). Strikingly, we detected the presence of MDA5-positive/hormone-negative endocrine islet-like clusters in T1D donors, presumably due to dedifferentiation or neogenesis phenomena. These clusters were identified exclusively in donors with recent disease onset and not in autoantibody-positive nondiabetic donors or donors with long-standing T1D. In conclusion, we showed that MDA5 is preferentially expressed in α-cells, and its expression is increased in recent-onset T1D donors. Finally, we observed that MDA5 may also characterize the phenotype of dedifferentiated or newly forming islet cells, thus opening to novel roles for MDA5 in pancreatic endocrine cells.